Refúgios climáticos de mamíferos marinhos - Almeida, Cecilia Silva da Rocha Pita de (2018)
Understanding how climate has shaped distribution of species over evolutionary time has been central to biogeographic studies. It is mean that climate change affects the survival of individuals, and therefore interferes in the structure of the community. We know that climate change varied considerably over time and space, and it is necessary to subjugate places so-called climatic refuges. These refuges, in turn, served as a shelter and protection of species by maintaining more stable conditions for their conservation and survival. In the marine environmental, one of the most strinking and no so far climatic changes was the last maximum glaciation (UMG, ~ 21,000-18,000 years), which had a lower sea level than at present. In this study, our objectives were: (i) to identify the marine climate refuges where there was co-occurrence of a high number of species in the three time periods (present: 0ka, 6 ka in middle Holocene and 21 ka in Pleistocene) in the marine environment; (ii) determine which ecological and historical factors characterize refuges. We obtained occurrence data for 110 species of marine mammals from the GBIF global repository and of specific articles to be constructed the species distribution models using the Maxent algorithm by program R 3.2.2. Four climatic variables were selected (annual mean sea surface salinity, annual mean sea surface temperature, annual range sea surface salinity and annual range sea surface temperature), which were obtained from the Model of Community Climate System, version 3 (CCSM3). The climatic refuges were determined as area that presented species richness above 90th percentile over the three time intervals. The location of these refuges was observed in temperate regions above latitudes 30˚, indicating that these areas presented conditions more suitable for most species. The ecological and historical factors that determined the refuges were tested with Mann-Whitney, using a significance of p <0.05. These refuges were related to ecological factors such as high productivity (p <0.001) and historical as high depth (p <0.001) and the presence of species with the highest mean evolutionary divergence time (p <0.001), meaning that the refuges harbored lineage of species older than non-refuge regions. Our results show a significant difference between the variables tested (p <0.05). Moreover, ecological and historical factors served as good predictors of species richness in the marine environment. It is noteworthy that this work is a pioneer in determining refuges for the marine environment and on a global scale, and should be more explored for other taxa. We suggest that the refuge identified here can be considered in the conservation policies of marine mammal species due to the ability of these areas to present suitability environmental conditions for species maintenance. In future studies, we suggest that MDE be used as a useful tool for choosing new potential areas for preservation considering that environmental changes are frequent.